DESIGN AS A FACTOR OF TEACHING FOREIGN LANGUAGES TO STUDENTS OF TECHNICAL HIGHER EDUCATION INSTITUTIONS - Kodirova, Gavkhar (Журнал иностранных языков и лингвистики, 2023)
In this work, design technology is considered as a factor in teaching foreign languages to future engineers in higher education institutions. The cognitive-developmental function of the educational project in relation to the components of learning foreign languages of future engineers is revealed in the context of the use of connections between subjects.